Pengaruh biaya lingkungan dan corporate social responsibility terhadap profitabilitas pada Perusahaan Sektor Kesehatan yang terdaftar di Indeks Saham Syariah Indonesia (ISSI) - Dwi Aini Safika, Nur; Ramadhani Irma Tripalupi; Ade Jamarudin (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2025)
This study aims to determine the effect of environmental costs and corporate social responsibility (CSR) on profitability in healthcare companies listed on the Indonesian Sharia Stock Index for the 2021-2024 period. This study employed a quantitative descriptive method with purposive sampling supported by secondary data drawn from annual reports and company sustainability reports. The results indicate that environmental costs partially have a significant positive effect on profitability, as measured by return on assets and return on equity. Furthermore, corporate social responsibility (CSR) partially has a negative but insignificant effect on profitability, as measured by return on assets and return on equity. Simultaneously, environmental costs and corporate social responsibility significantly influence profitability, as measured by return on assets and return on equity.